Global hotspots and trends in microbial-mediated grassland carbon cycling: a bibliometric analysis - Xiang, Xing; Yao, Tuo; Man, Baiying; Lin, Dong; Li, Changning (Frontiers in Microbiology, 2024)
Grasslands are among the most widespread environments on Earth, yet we still have poor knowledge of their microbial-mediated carbon cycling under the context of human activity and climate change. We conducted a systematic bibliometric analysis of 1,660 literatures focusing on microbial-mediated grassland carbon cycling in the Scopus database from 1990 to 2022. We observed a steep increase in the number of multidisciplinary and interdisciplinary studies since the 2000s, with focus areas on the top 10 subject categories, especially in Agricultural and Biological Sciences. Additionally, the USA, Australia, Germany, the United Kingdom, China and Austria exhibited high levels of productivity. We revealed the eight papers have been pivotal in shaping future research in this field, and the main research topics concentrate on microbial respiration, interaction relationships, microbial biomass carbon, methane oxidation and high-throughput sequencing. We further highlight that the new research hotspots in microbial-mediated grassland carbon cycling mainly focused on the keywords of "carbon use efficiency", "enzyme activity", "microbial community" and "high throughput sequencing". Our bibliometric analysis in the past three decades provides insights into a multidisciplinary and evolving field of microbial-mediated grassland carbon cycling, not merely summarizing the literature but also critically identifying research hotspots and trends, intellectual base, and interconnections within the existing body of collective knowledge, and signposting the path for future research directions.